Primary disseminated MDR-TB in a Bangladeshi man: a silent and emerging clinical problem for clinicians. (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):719-23 The abstract of this article is available on the PubMed website